Age at Pubertal Onset in Girls and Tobacco Smoke Exposure During Pre- and Postnatal Susceptibility Windows. Issue 5 (September 2017) - Windham, Gayle C.; Lum, Raymond; Voss, Robert; Wolff, Mary; Pinney, Susan M.; Teteilbaum, Susan L.; Sosnoff, Connie S.; Dobraca, Dina; Biro, Frank; Hiatt, Robert A.; Greenspan, Louise C.; Galvez, Maida; et al.
Abstract : Background: Tobacco smoke contains known hormonally active chemicals and reproductive toxicants. Several studies have examined prenatal maternal smoking and offspring age at menarche, but few examined earlier pubertal markers, nor accounted for exposure during childhood. Our objective was to examine pre- and postnatal smoke exposure in relation to timing of early pubertal events. Methods: An ethnically diverse cohort of 1239 girls was enrolled at age 6–8 years old for a longitudinal study of puberty at three US sites. Girls participated in annual or semi-annual exams to measure anthropometry and Tanner breast and pubic hair stages. Prenatal and current tobacco smoke exposures, as well as covariates, were obtained from parent questionnaire. Cotinine was measured in urine collected at enrollment. Using accelerated failure time models, we calculated adjusted time ratios for age at pubertal onset (maturation stages 2 or higher) and smoke exposure. Results: Girls with higher prenatal (≥5 cigarettes per day) or secondhand smoke exposure had earlier pubic hair development than unexposed (adjusted time ratio: 0.92 [95% CI = 0.87, 0.97] and 0.94 [95% CI = 0.90, 0.97], respectively). Including both exposures in the same model yielded similar associations. Higher urinary cotinine quartiles were associated with younger age at breast and pubic hair onset in unadjusted models, but not after adjustment. Conclusions: Greater prenatal and childhood secondhand smoke exposure were associated with earlier onset of pubic hair, but not breast, development. These exposures represent modifiable risk factors for early pubertal development that should be considered for addition to the extensive list of adverse effects from tobacco smoke. Abstract : Supplemental Digital Content is available in the text.